Syringomyelia and its treatment - A case report - Siti Musfiroh Siti Musfiroh (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
Syringomyelia is a chronic progressive degenerative disorder of the spinal cord, characterized clinically by brachial amyotrophy and segmental sensory loss of dissociated type. Pathologically shows cavitation in the central parts of the spinal cord, usually at the cervical region but extending upward into medulla oblongata and pons or downward into the thoracic or even the lumbar segments. This disorder doesn't product weakness of the limb. The early symptom, was weighty and stiffness of the neck, and painful of the right arm. After four years her right shoulder was pain too and there was anesthesia, with Magnetic Resonance Imaging we knew that she had syringomelia in the carvical area. She became exellent outcome after shunting. Conclusion : the case was the shoulder arm syndrom case with segmental anesthesia which was becoming worst, it should be suspecious of syringomelia and it must be treated by establishing shunt.key word : syringomyelia - brachial amyotrophy - anesthesia - magnetic resonance imaging.